GE_GERICHTE PS/34/2014 vom 28. Oktober 2014 - GE Cour de justice (2014)
CONTRAVENTION; CLASSEMENT DE LA PROCÉDURE; ACCIDENT DE LA CIRCULATION; VOIES DE FAIT; FARDEAU DE LA PREUVE | CPP.357; CPP.310; CP.126